Corporate Communication: A Guide to Theory And Practice - Cornelissen, Joep (London Sage, 2023)
"This popular, market-leading textbook for corporate communication continues to be the authoritative and definitive textbook for students and educators. The text has been fully updated to include: - changes to the workplace in light of the Covid-19 pandemic and its impacts on employee communication via platforms such as Zoom and Microsoft Teams - the ongoing impacts of digital disruption and transformation on corporate communication at the advent of the 'metaverse' and alongside consideration of popular newer social media such as TikTok - the increasing focus on sustainability and the United Nations' Sustainable Development Goals (SDGs); societal impact, purpose and corporate social responsibility; and the importance of social justice and inclusion within organizations and how these relate to organizational communication New case studies include Black Lives Matter (Starbucks); surveillance capitalism (Facebook); diversity and inclusion (Microsoft); and hybrid working (British Airways). This textbook is essential reading for communication courses including: corporate communication; organizational communication; management communication; strategic communication; and public relations. Joep Cornelissen is Professor of Corporate Communication and Management at Rotterdam School of Management, Erasmus University"--
Keywords: Corporate Communication; Business communication ; Communication in management